Mona Lisa is always happy - and only sometimes sad. - Liaci, Emanuela; Fischer, Andreas; Heinrichs, Markus; van Elst, Ludger Tebartz; Kornmeier, Jürgen (Scientific reports, 2017)
The worldwide fascination of da Vinci's Mona Lisa has been dedicated to the emotional ambiguity of her face expression. In the present study we manipulated Mona Lisa's mouth curvature as one potential source of ambiguity and studied how a range of happier and sadder face variants influences perception. In two experimental conditions we presented different stimulus ranges with different step sizes between stimuli along the happy-sad axis of emotional face expressions. Stimuli were presented in random order and participants indicated the perceived emotional face expression (first task) and the confidence of their response (second task). The probability of responding 'happy' to the original Mona Lisa was close to 100%. Furthermore, in both conditions the perceived happiness of Mona Lisa variants described sigmoidal functions of the mouth curvature. Participants' confidence was weakest around the sigmoidal inflection points. Remarkably, the sigmoidal functions, as well as confidence values and reaction times, differed significantly between experimental conditions. Finally, participants responded generally faster to happy than to sad faces. Overall, the original Mona Lisa seems to be less ambiguous than expected. However, perception of and reaction to the emotional face content is relative and strongly depends on the used stimulus range.
Keywords: *Facial Expression; *Museums; *Paintings; Adult; Analysis of Variance; Emotions; Female; Happiness; Humans; Male; Perception; Reaction Time; Young Adult

Perceptibility of simulated VLF-sferics - Klöpper, R.; Stark, R.; Schienle, A.; Vaitl, D. (Perceptual and Motor Skills, 2001)
Sferics are weak, naturally occurring electromagnetic fields related to specific weather conditions. There are some hints that these signals might be responsible for certain complaints that are often described as "weather sensitivity syndrome." The study's purpose was to find out whether humans, when exposed to simulated sferics, can consciously perceive any kind of psychophysiological changes. 63 subjects were trained within a simple learning paradigm to discriminate between phases where simulated sferics were present or absent. They were reinforced for each correct decision out of 80 judgements by means of acoustic signals. A reward of 100 German marks was pledged to the participant who would achieve the best result of the total sample. The total number of correct judgements did not differ from a random run and no learning occurred. Subjects who reported fewer bodily complaints in their recent past had higher scores in the discrimination task.
Keywords: Adult; Decision Making; Discrimination Learning; Electromagnetic Fields; Female; Humans; Judgment; Male; Perception; Personality; Psychophysics; Random Allocation; Time Factors

Interoception - Vaitl, D. (Biological Psychology, 1996)
During the last two decades, research on interoception has experienced a surprising renaissance. New experimental approaches and methods have revealed much about the processing of afferent signals from the inner organs of the body, and have allowed more accurate descriptions of these processes, as well as a more accurate determination of their functional significance in the experience and behavior of humans. Besides neuromuscular, respiratory, and gastrointestinal interoceptive processes, the cardiovascular afferent influences are now known to be very important. Invariably, the central questions concern sensitivity to signals from the body, factors which may influence judgement of perception, and the degree to which conventional hypotheses regarding the interoceptive capabilities of humans may require revision. Findings from general psychological and clinical studies have shown that humans may attain remarkable levels of interoceptive performance. On the other hand, they also show how deep the chasm is between visceral processes and perception, and between that which is perceived and the reports thereof. Only interdisciplinary approaches to these complex processes promise success.
Keywords: Autonomic Nervous System; Awareness; Digestive System Physiological Phenomena; Female; Heart Rate; Humans; Male; Perception; Proprioception; Respiration; Sensory Receptor Cells; Viscera; Visceral Afferents

Simulated micro-gravity and cortical inhibition: a study of the hemodynamic-brain interaction - Vaitl, D.; Gruppe, H.; Stark, R.; Pössel, P. (Biological Psychology, 1996)
The present study was carried out to determine the inhibitory cortical processes induced by changes in hemodynamics. Previous experiments in humans conducted in our laboratory have shown that there is a close relationship between posture and delta and theta EEG activity. The most pronounced effects were obtained during the 6 degrees head-down tilt (HDT) position. In space medicine the HDT procedure is very frequently employed to simulate micro-gravity and to determine the neurohormonal counter-regulations evoked by the expansion of central volume. Twenty male subjects spent 23 h in bed in 6 degrees HDT and 23 h in 6 degrees HUT (head-up tilt) positions during which EEG (frontal, central, parietal, occipital), startle responses, and reaction-times were measured every 2 h (from 10:00 h till 20:00 h). The effects of cardiovascular deconditioning (CD) regularly occurring after HDT were assessed by examining orthostatic tolerance and the physical work capacity (bicycle ergometry). As expected, 23 h HDT led to more pronounced CD than HUT. Spectral power analyses of EEG revealed increases in delta and theta frequency hands similar to those found during HDT in previous EEG studies. In addition, subjects responded more slowly (S1-S2 reaction-time task) during HDT as compared with HUT bedrest. The influence of HDT on startle response, however, was not in keeping with the initial hypothesis (i.e. dampening of reflex activity). The EEG data and the sensorimotor performance indicated that the body fluid shift towards the thoracic cavity induced by HDT resulted in signs of cortical inhibition. In addition to neural mechanisms, other processes must be postulated which are closely related to the counter-regulation evoked by the varying body positions.
Keywords: Adult; Cerebral Cortex; Delta Rhythm; Electroencephalography; Gravitation; Hemodynamics; Homeostasis; Humans; Male; Neural Inhibition; Perception; Posture; Pressoreceptors; Proprioception; Reaction Time; Reference Values; Reflex; Reflex; Startle; Theta Rhythm; Weightlessness